TEKNIK DAN ALAT BANTU DALAM PENGAMBILAN KEPUTUSAN OLEH KEPALA SEKOLAH: TINJAUAN LITERATUR DALAM KONTEKS MANAJEMEN PENDIDIKAN - Susanto, Teguh Trianung Djoko; Zakiati, Dyah; Fitriyani Haryanto, Endah; Apriliansyah, Farhan (STKIP Pesisir Selatan, 2025)
This article aims to analyze the effectiveness of implementing quantitative and qualitative techniques in the decision-making process of school principals within the context of educational management. This study employs a Systematic Literature Review (SLR) approach, structured based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol to ensure transparency and accuracy in the selection and analysis of literature. A total of 45 national and international scientific articles published between 2015 and 2024 were thematically reviewed based on the type of technique used, the context of implementation (such as program planning, budget allocation, performance evaluation, and curriculum development), and the effectiveness indicators reported in each study. The analysis reveals that the integration of quantitative techniques such as the Analytical Hierarchy Process (AHP) and descriptive statistics, with qualitative techniques like Delphi and Focus Group Discussions (FGD), can lead to more targeted, adaptive, inclusive, and responsive decisions to school needs. This integration also encourages stakeholder participation and enhances policy transparency. The novelty of this study lies in the comprehensive mapping of integrative decision-making techniques in schools, which is still rarely discussed systematically in Indonesian literature.